2023
DOI: 10.21203/rs.3.rs-2621698/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Examining parent-of-origin effects on transcription and RNA methylation in mediating aggressive behavior in honey bees (Apis mellifera)

Abstract: Conflict between genes inherited from the mother (matrigenes) and the father (patrigenes) is predicted to arise during social interactions among offspring if these genes are not evenly distributed among offspring genotypes. This intragenomic conflict drives parent-specific transcription patterns in offspring resulting from parent-specific epigenetic modifications. Previous tests of the kinship theory of intragenomic conflict in honey bees (Apis mellifera) provided evidence in support of theoretical predictions… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 110 publications
1
5
0
Order By: Relevance
“…Our results provide support for the model of intragenomic conflict altering phenotypes by cascading impacts on downstream GRNs, versus directly altering expression of a single gene with major effects (Patten et al, 2016). As in previous studies in bees (Bresnahan et al, 2023;Galbraith et al, 2016Galbraith et al, , 2021Marshall et al, 2020), there was little overlap between genes that showed parent-biased expression and genes whose overall expression differences were associated with behavioural variation. However, our SVM and the combined set of genes showing parent-biased expression both showed overrepresentation for genes encoding proteins with DNA binding function, including several TFs.…”
Section: Genes Showing Intragenomic Conflict Are Found Within Gene Ne...supporting
confidence: 83%
See 3 more Smart Citations
“…Our results provide support for the model of intragenomic conflict altering phenotypes by cascading impacts on downstream GRNs, versus directly altering expression of a single gene with major effects (Patten et al, 2016). As in previous studies in bees (Bresnahan et al, 2023;Galbraith et al, 2016Galbraith et al, , 2021Marshall et al, 2020), there was little overlap between genes that showed parent-biased expression and genes whose overall expression differences were associated with behavioural variation. However, our SVM and the combined set of genes showing parent-biased expression both showed overrepresentation for genes encoding proteins with DNA binding function, including several TFs.…”
Section: Genes Showing Intragenomic Conflict Are Found Within Gene Ne...supporting
confidence: 83%
“…The KTIC predicts that selection should favour a balance between the individual effects of matrigenes and patrigenes engaged in conflict (Haig, 2008;Patten et al, 2016). In support of this prediction, previous studies in honey bees-which demonstrated that patrigenes favour the selfish behaviours of worker ovary activation (Galbraith et al, 2016(Galbraith et al, , 2021 and aggression (Bresnahan et al, 2023)-found that genes showing differences in parent-specific transcript abundance do not show differences in overall transcript abundance, presumably because upregulation of one allele was balanced by downregulation of the other allele. If the total amount of transcript for a given gene is the same between two behavioural phenotypes, how do genes engaged in parent-of-origin conflicts contribute to variation in physiology or behaviour?…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Thus, matrigenes and patrigenes are unevenly distributed among nestmates and should experience different selective pressures leading to POEs on transcription (Queller, 2003). Such parent-of-origin intragenomic conflicts have been demonstrated in association with behavioral variation in adult worker honey bees (Bresnahan et al, 2023a(Bresnahan et al, , 2023bGalbraith et al, 2016aGalbraith et al, , 2021Gibson et al, 2015;Kocher et al, 2015), and in the transcriptomes of diploid eggs laid by queens (Smith et al, 2020).…”
Section: Introductionmentioning
confidence: 99%